Apparent diffusion coefficient and fractional anisotropy in the vertebral bone marrow - Ueda, Yu; Miyati, Tosiaki; Ohno, Naoki; Motono, Yuko; Hara, Masaki; Shibamoto, Yuta; Kasai, Harumasa; Kawamitsu, Hideaki; Matsubara, Kosuke (Journal of magnetic resonance imaging, 2010)
Purpose: To assess the state of cancellous tissue we analyzed the apparent diffusion coefficient (ADC) and fractional anisotropy (FA) in vertebral bone marrow. Materials and Methods: With 1.5 T magnetic resonance imaging (MRI), single‐shot diffusion echo planar imaging was used with b factors of 0 and 1000 s/mm2, diffusion‐sensitizing gradient in six directions, sensitivity encoding technique, effective TE of 74 msec, and TR of 1800 msec. ADC and FA were determined in the lumbar vertebral body of 11 normal subjects (age 31 632–635 years), and then compared with the bone mineral density (BMD) obtained with dual‐energy x‐ray absorptiometry (DXA). Moreover, fat fraction (FF) of the bone marrow was measured with spectral presaturation with inversion recovery (SPIR) in the same subject. Results: A strong negative correlation was found between ADC and BMD for low or moderate FF in vertebral bone marrow. Moreover, a significant positive correlation was noted between ADC and FF in this region. There was a positive correlation between FA and BMD, and no correlation between FA and FF in the vertebral bone marrow. Conclusion: Diffusion analyses with ADC and FA make it possible to obtain more detailed information on the structure of cancellous tissue and bone metabolism. J. Magn. Reson. Imaging 2010;31:632–635. © 2010 Wiley‐Liss, Inc.